Relative contribution of the magnetic field barrier and solar wind speed in ICME-associated forbush decreases - Bhaskar, Ankush; Subramanian, Prasad; Vichare, Geeta (My University, 2016)
We study 50 cosmic-ray Forbush decreases (FDs) from the Oulu neutron monitor data during 1997–2005 that were associated with Earth-directed interplanetary coronal mass ejections (ICMEs). Such events are generally thought to arise due to the shielding of cosmic rays by a propagating diffusive barrier. The main processes at work are the diffusion of cosmic rays across the large-scale magnetic fields carried by the ICME and their advection by the solar wind. In an attempt to better understand the relative importance of these effects, we analyze the relationship between the FD profiles and those of the interplanetary magnetic field (B) and the solar wind speed (Vsw). Over the entire duration of a given FD, we find that the FD profile is generally (anti)correlated with the B and Vsw profiles. This trend holds separately for the FD main and recovery phases too. For the recovery phases, however, the FD profile is highly anti-correlated with the Vsw profile, but not with the B profile. While the total duration of the FD profile is similar to that of the Vsw profile, it is significantly longer than that of the B profile. Using the convection– diffusion model, a significant contribution of advection by solar wind is found during the recovery phases of the FD.
Keywords: Solar terrestrial relations; Sun; Solar wind; Coronal mass ejection; Convection; Cosmic rays; CME; Magnetic fields